EFFORTS TO INCREASE COFFEE STORE BUSINESS INCOME THROUGH FINANCIAL LITERATURE DURING THE COVID-19 PANDEMIC: Article - Christina Heti Tri Rahmawati; Rubiyatno Rubiyatno; Theodorus Sutadi (LPPM Universitas Wijaya Putra, 2022)
The existence of a coffee shop (warkop) as a business option for the community is very easy to find where it serves coffee of various types. The ease of entering the coffee shop market has an impact on the competition between coffee shops in obtaining increasingly fierce consumers. The COVID-19 pandemic also has an impact on the sustainability of coffee shops because income has decreased and cannot finance business operations. Micro, Small and Medium Enterprises (MSMEs) coffee shops who have good financial literacy will be able to manage finances and increase business income. This community service aims to provide assistance to coffee shop business actors, especially in Omak Kopi SMEs regarding financial literacy and financial management. The results of this assistance are MSME actors Omak Kopi (1) have financial literacy in the medium category including financial institution service products to invest by saving, making loans, and insurance; and (2) able to perform financial management by making good financial records. This assistance has implications for increasing financial literacy and managing business finances which in turn increases the income of MSME actors during the COVID-19 pandemic. Financial Literacy; Business Income; Coffee Shop